The Modern Girl and the Lady: Negotiating Modern Womanhood in a South African Magazine, 1910-1920 - Venter, Isabella J. (South African Historical Journal, 2019)
The aim of this paper is to provide an overview of how the definition of the ideal 'modern' woman changed in South Africa for white middle- and upper-class women. Many of the changes in the definition of the ideal woman were appropriated from Britain, but the definition also differed. In general, these differences have been overlooked by academia as there is a prevailing assumption that South African women's views on gender either reflected British trends or differed only in terms of the suffrage movement and racial views. I argue that studying popular magazines and literature at the time will provide a clearer indication of how women negotiated their roles as these are polyphonic texts that do not merely reflect one author's view. Using an intertextual approach this study looks at a popular magazine from the time, the South African Lady's Pictorial and Home Journal, as well as several of the South African novels reviewed in the magazine to trace the conversation over the period in question. Through discourse analysis, major trends and changes in those trends have been identified to show how white English-speaking women defined womanhood at a time when there were great changes and challenges to gender norms.